Cardiac MRI e-prime predicts myocardial late gadolinium enhancement and diastolic dysfunction in hypertrophic cardiomyopathy. Issue 149 (April 2022) - O'Brien, Amy C.; MacDermott, Roisin; Keane, Stephen; Ryan, David T.; McVeigh, Niall; Durand, Rory; Ferre, Maria; Murphy, David J.; Teekakirikul, Polakit; Keane, David; McDonald, Ken; Ledwidge, Mark; et al.
Highlights: Cardiac MRI e′ measures the mitral annular velocity during ventricular relaxation (CMR e′) Cardiac MRI e′ independently predicts ≥10% myocardial late gadolinium enhancement in HCM. Cardiac MRI e′ independently predicts feature tracking parameters of diastolic dysfunction in HCM. Abstract: Background: Myocardial fibrosis leads to diastolic dysfunction in patients with hypertrophic cardiomyopathy (HCM). Objectives: To evaluate a manual method of measuring mitral annular relaxation velocity (termed cardiac MRI e′) as a measure of diastolic dysfunction on routine cardiac MRI and its relationship with myocardial late-gadolinium enhancement (LGE) and feature tracking measures of diastolic dysfunction in patients with HCM. Methods: CMR e′, feature tracking measures of diastolic function, left atrial, left ventricular (LV) parameters and LGE were retrospectively measured in 75 patients with HCM (mean age, 54.7 years ± 15.3, 54 men). Multivariate regression and partial Spearman correlations were performed. Results: Cardiac MRI e′ measures correlated with LGE (r = 0.49, P < 0.001) and multiple feature tracking measures of diastolic function, adjusted for patient demographics, left atrial and left ventricular parameters. Cardiac MRI e′ measures were independently predictive of LGE ≥ 10% (mean total cardiac MRI e′: LGE < 10% vs LGE ≥ 10% was 3.5 cm/s vs. 1.7 cm/s, P < 0.001). Superior CMR e′ had an AUC of 0.79 [95%CI 0.66–0.92, P < 0.0001]) in predicting patients with LGE ≥ 10% and a cutoff of 1.7 cm/s resulted in a sensitivity and specificity of 81.0% and 78.0% respectively. Conclusion: Cardiac MRI e′ is a manual measure of LV diastolic dysfunction acquired on routine cardiac MRI without specialized software and is an independent predictor of LGE ≥ 10% and diastolic dysfunction in HCM.